The effect of different forms of intravitreal ranibizumab administration on pain (Annals of Medical Research, 2024)
Aim: To examine the effect of using the prefilled syringe formulation of intravitreal ranibizumab (ivr) on pain.Materials and Methods: 30 patients received bilateral IVR injection due to diabetic retinopathy and macular edema and 30 eyes of these patients that received ready-to-use (PFS) IVR were considered as group 1, and the 30 eyes that received conventional IVR by withdrawing from the vial were considered as group 2. Patients who had previously received intravitreal injection, had intraocular surgery, used any eye drops, and were unable to cooperate with the assesment were excluded from the study. Pain experienced during the injection was assessed by using the numerical rating scale (NRS) and the verbal rating scale (VRS).Results: The mean age of 30 female patients evaluated was 60.3±7.94 years. While the NRS was 3.70±0.79 in Group 1, it was 4.23±0.77 in Group 2, the difference was statistically significant (p=0.02). While the VRS  was 2.13±0.34 in Group 1, it was found to be 3.0±0.58 in Group 2, the difference was statistically significant (p=0.02).Conclusion: IVR application in ready-to-use formulation causes less pain during intravitreal injection.